Cross-tissue transcriptome-wide analysis reveals novel insights into thyroid cancer etiology - Yue Zhu; Yu Luo; Yuye Zhang; Yixuan Wang; Zhangqi Gu; Jinyan Liu; Ancheng Qin; Weifeng Qian (Discover Oncology)
Abstract Background Despite significant advances made by genome-wide association studies (GWAS) in the genetic exploration of tumors such as thyroid cancer (TC), the precise pathogenic genes and underlying biological mechanisms of TC remain unclear. Methods We performed a transcriptome-wide association study (TWAS) to identify the susceptibility genes for TC. Three complementary methods: FUSION (Functional Summary-based Imputation), FOCUS (Fine-mapping Of CaUsal gene Sets), and Multi-marker Analysis of GenoMic Annotation (MAGMA) were used to validate key gene discoveries. Additionally, MAGMA was used to examine the functional enrichment of single nucleotide polymorphisms (SNPs) associated with TC. Conditional and joint analysis, as well as fine mapping techniques, were employed to deepen our understanding of TC’s genetic architecture. To explore causal relationships, we conducted Mendelian randomization analysis, while colocalization analysis was used to provide potential shared SNPs between key genes and TC risk. Results Through the comprehensive application of three TWAS methods, we identified three potential susceptibility genes closely associated with TC risk. Mendelian randomization analysis provided causal links between the TGFB2, SMAD3 and SDCCAG8 genes and TC. Colocalization analysis further revealed that TGFB2 (rs1764705), SMAD3 (rs17293632), and SDCCAG8 (rs2490395) may share genetic signals between GWAS and expression quantitative trait loci (eQTL), indicating common pathways in TC pathogenesis. The study highlighted differences in the expression of significant genes in normal and thyroid cancer tissues at the transcriptome level and investigated their relationship with the tumor microenvironment. Conclusion This investigation uncovered three new genes associated with increased TC risk, shedding light on the genetic underpinnings of TC and aiding in a deeper comprehension of its complex genetic architecture.